The Passivation Behavior of Sputter-deposited W-Zr Alloys in NaCl and NaOH Solutions - Shrestha, Prakash; Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2010)
The passivation behavior of the sputter-deposited amorphous or/and nanocrystallineW-Zr alloys is studied in 0.5 M NaCl and 1 M NaOH solutions at 25°C, open to air usingcorrosion tests and electrochemical measurements. Zirconium metal acts synergisticallywith tungsten in enhancing the corrosion resistance of the sputter-deposited W-Zr alloys soas to show lower corrosion rates than those of alloy-constituting elements (that is, tungstenand zirconium) in 0.5 M NaCl solution. In particular, corrosion rates of the binary W-Zralloys containing 23-76 at % zirconium are more than one order of magnitude lower thanthat of tungsten (that is, about 0.8-1.1 × 10-3 mm.y-1) and even lower than that of the sputterdepositedzirconium. On the other hand, the corrosion rates of the W-Zr alloys containing54-76 at% zirconium are nearly two orders of magnitude lower than that of tungsten andeven about one order of magnitude lower corrosion rate than that of sputter-depositedzirconium metal in alkaline 1 M NaOH solution. These results clearly revealed that thesimultaneous additions of both tungsten and zirconium metals to the sputter-depositedamorphous or nanocrystalline W-Zr alloys are effective in enhancing the corrosionresistance of the alloys in both 0.5 M NaCl and alkaline 1 M NaOH solutions at 25°C, opento air. The corrosion-resistant of all the examined binary W-Zr alloys in 0.5 M NaClsolution is higher than in 1 M NaOH solution at 25°C. In general, the open circuit potentialsof all the examined W-Zr alloys are shifted to more noble direction with increasing the alloyzirconium content in both 0.5 M NaCl and 1 M NaOH solutions.Keywords: Sputter-deposited W-Zr alloys, amorphous, corrosion test, electrochemicalmeasurement, NaCl and NaOH solutions.DOI:  10.3126/jncs.v25i0.3283Journal of Nepal Chemical Society Volume 25, 2010 pp 37-45